ANALISIS KADAR BETA KAROTEN DAN VITAMIN C BUAH JUWET (Syzigium cumini ) secara SPEKTROFOTOMETRI UV-VIS - Panji Ratih Suci; Nadya Hapsari; Reny Dwi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Beta-carotene (?-Carotene) is an organic compound and is classified as a terpenoid. ?-Carotene is a red-orange pigment that is very abundant in plants and fruits. Beta-carotene is thought to have many functions that other compounds do not have (Subawati, 2009). The aim of this study was to determine ?-carotene levels in juwet fruit (Syzygium Cumini) by UV-Vis spectrophotometry. Juwet fruit samples (Syzygium Cumini) were extracted with acetone as a solvent. The extract obtained was extracted again with petroleum ether solvent, then saponified with 15% KOH solvent in methanol. The extract was liberated with distilled water. The extract obtained was dried over anhydrous Na2SO4. The extract obtained was analyzed qualitatively using Thin Layer Chromatography, and UV-Vis spectrophotometry at a wavelength of 332.1539 nm. The average level of ?-carotene in juwet fruit was 1.25 mg. Analysis of Vitamin C levels was carried out at a wavelength of 265.3 nm, the average level of Vitamin C in juwet fruit was 1.473